Between burden and bridge: Metaphorical framing of accent among international students in China - Awaisuddin,; Haitao Miao,; Saleem, Amjad (Journal of International Students, 2026)
Learning a new language is central to both the academic and sociocultural adjustment of international students. Accent, in particular, represents a key site of emotional and identity negotiation. Drawing on conceptual metaphor theory (Lakoff & Johnson, 1980) and framing theory (Goffman, 1974), this study explores how international students in China conceptualize and experience their Mandarin accent. On the basis of metaphor-elicitation interviews with 25 international students from diverse linguistic backgrounds, the findings suggest the presence of two dominant and contrasting metaphorical frames; the ‘Burden/Barrier’ frame is associated with anxiety, frustration, and perceived social distance, whereas the ‘Bridge/Tool’ frame reflects meanings of access, identity, and agency. These metaphorical framings appear to shape how learners interpret their communicative experiences, negotiate identity, and position themselves socially. The results of this study suggest that accents may function as a cognitive filter through which aspects of the international students’ experiences are interpreted.